Radio wars : broadcasting during the Cold War - Risso, Linda (London ; New York : Routledge, Taylor & Francis Group, 2017)
"The chapters gathered here investigate both the institutional history of the radio broadcasting corporations in the East and in the West, and their relationship with other propaganda agencies of the time. they examine the 'off-air' politics of radio broadcasting, from the choice of theme to th e selection of speakers, singers and music pieces. The key issue tackled by contributors is the problem of measuring the impact of, and qualifying the success of, information policies and propaganda programmes produced during the cultural Cold War."--First fly leaf.
1. 'A hideously difficult country': British propaganda to France in the early Cold War / Hilary Footitt -- 2. Did the RAI buy it? The role and limits of American broadcasting in Italy in the Cold War / Simona Tobia -- 3. Voices, letters, and literature through the Iron Curtain: exiles and the (trans) mission of radio in the Cold War / Friederike Kind-Kovács -- 4. Cold War radio and the Hungarian uprising, 1956 / Alban Webb -- 5. Captive audience? GDR radio in the mirror of listeners' mail / Christoph Classen -- 6. Listening behind the curtain: BBC broadcasting to East Germany and its Cold War echo / Patrick Major.
Includes bibliographical notes and index, p. 133-140.
Keywords: Radio in propaganda -- History -- 20th century; Cold War -- Propaganda; International broadcasting -- History -- 20th century